Syndrome Leigh caused by mutations in the SURF1 gene: clinical and molecular-genetic characteristics - Tsygankova, P G; Mikhaĭlova, S V; Zakharova, E Iu; Pichkur, N A; Il'ina, E S; Nikolaeva, E A; Rudenskaia, G E; Dadali, E L; Kolpakchi, L M; Fedoniuk, I D; Matiushchenko, G N (Zhurnal nevrologii i psikhiatrii imeni S.S. Korsakova, 2010)
Syndrome Leigh (SL) or subacute necrotizing encephalomyelopathy - is a rare hereditary genetically heterogeneous disease from the group of mitochondrial encephalomyopathies. Twenty-seven children with SL were examined using clinical, laboratory (measuring lactate levels), MRI and molecular-genetic (polymerase chain reaction genotyping of 9 exons of the SURF1 gene) studies. The mean age of manifestation was 11,6 months. The main manifestations of SL were: delay of psychomotor development, diffuse muscle hypertonic, cerebellar syndrome, ophthalmoparesis, hypertrichosis. The disease had a progressive course with the loss of acquired skills. The blood lactate concentration was increased on average up to 3,1 mM/ml (from 1,9 to 5,1 mM/ml) compared to normal values (1,8 mM/ml). Brain MRI revealed the subcortical and cortical atrophy (80% of cases), symmetrical distinctly delineated hyperintense lesions on T2-weighted images (demyelization) in the basal ganglia and the brain stem (50%), as well as in the cerebellum (25%). Genotyping identified 7 different mutations. The most frequent (64,8%) was the deletion of 2 nucleotides (845delCT) in exon 8 that was in line with early data of Polish researchers thus indicating the Slavic origin of this mutation. Other mutations (574-575insCTGT, 311-321del10insAT and IVS8-1G>) were also frequent in the Russian population.